Enamel remineralisation prospect of Moringa Oleifera hydrogel, eggshell hydrogel versus sodium fluoride varnish on artificially demineralised primary teeth: in vitro study - Mona Essam Eliwa; Yousra Mohamed; Ehsan Hossam (Medical Journals Sweden, 2024)
Purpose: The purpose of the present in vitro study is to investigate and compare the remineralising potential of Moringa Oleifera extract, eggshell, and sodium fluoride varnish on microhardness of artificially demineralised enamel of primary teeth with biomimetic minimally invasive approach following the world paradigm shift towards natural products in paediatric dentistry. Material and methods: Sample size included 44 primary molars. The mineral content and surface microhardness of all specimens were initially assessed using energy dispersive x-ray examination (EDX) and Vickers microhardness. The specimens were artificially demineralised for 96 h at a temperature of 37°C and then reassessed directly after demineralisation. The demineralised enamel specimens were randomly divided into four groups according to the remineralisation regimen utilised. Group 1: Artificial saliva (control); Group 2: Sodium fluoride varnish; Group 3: Eggshell hydrogel; and Group 4: Moringa Oleifera hydrogel. The specimens were stored for 8 days and then subsequently evaluated using EDX and microhardness assessment by Vickers microhardness test and scanning electron microscope (SEM).  Results: Regarding the microhardness test, there was a significant difference between the Moringa Oleifera group and Eggshell group compared to fluoride varnish (p < 0.05). Regarding EDX analysis, there was a statistically significant difference (p < 0.05) between Moringa Oleifera group and Eggshell group compared to fluoride varnish as the highest values were for Moringa Oleifera and Eggshell. On the other hand, there was no statistically significant difference (p > 0.05) between Moringa Oleifera and Eggshell in both the measurements. Conclusion: Moringa Oleifera and Eggshell might be considered as a biomimetic natural material capable of guiding enamel tissue remineralisation in early carious lesion of primary teeth. Clinical relevance: This research demonstrated the capability for early enamel caries to be remineralised using novel materials with a naturally counterpart implicated in biomineralisation as proved to be more effective than traditionally used fluoride varnish in primary teeth.